Pengaruh Pemberian Pupuk Organik Cair dan SP-36 Terhadap Pertumbuhan Bayam Merah (Amaranthus tricolor L.) - Justin Oberlin Hia; Eri Samah; Lutfi Henderlan Harahap (UNIVERSITAS LABUHANBATU, 2026)
This study aims to determine the effect of liquid organic fertilizer (POC) from cow urine and SP-36 fertilizer on the growth and yield of red spinach (Amaranthus tricolor L.). The study used a completely randomized design (CRD) with POC concentration treatments (P0, P1, P2, P3, P4, P5) and SP-36 concentrations (S0, S1, S2, S3, S4, S5). The parameters observed included plant height, number of leaves, leaf width, and root length. The results showed that increasing the concentration of POC from cow urine and SP-36 fertilizer significantly increased all plant growth parameters. POC from cow urine gave better results on shoot growth, while SP-36 tended to be more effective in increasing root length. The highest concentrations (P5 and S5) provided optimal growth results, with plant heights reaching 54.46 cm (POC) and 54.40 cm (SP-36), and dry weight reaching 8.1 g/stem. The conclusion of this study is that both types of fertilizer can be used to increase red spinach productivity, and their combination has the potential to provide a synergistic effect. Keywords: Red spinach, liquid organic fertilizer, cow urine, SP-36, plant growth